Polyaniline/Graphitic Carbon Nitride Nanocomposites with Improved Thermoelectric Properties - Ugraskan, Volkan; Karaman, Ferdane (SPRINGER, 2021)
In this study, we aimed to investigate the effects of graphitic carbon nitride (g-C3N4) on the thermoelectric (TE) properties of camphorsulfonic acid (CSA) doped polyaniline (PANI). For this purpose, g-C3N4 was synthesized at 550 degrees C using guanidine hydrochloride as a precursor. Later, PANI was synthesized by oxidative chemical polymerization and doped with CSA. Finally, PANI-CSA/g-C3N4 composites were prepared by ultrasonic homogenization with different weight ratios of g-C3N4. The composites showed positive Seebeck coefficients which are the characteristics of p-type semiconductors. The Seebeck coefficient of PANI-CSA enhanced from 10 mu V K-1 to 472 mu V K-1 with the incorporation of g-C3N4. Furthermore, the power factor (PF) of the composites reached a maximum at 70.75 mu W m(-1) K-2 which is almost 500 times higher compared to pristine PANI-CSA. This indicates that g-C3N4 is a promising additive to be used in polymer-based TE materials that can be used around room temperature.
Keywords: Polyaniline; graphitic carbon nitride; thermoelectric; composite; Engineering; Materials Science; Physics